The efficiency of construction terms insurance and commissioning of transport communications - A. S. Millerman; O. A. Bondarenko (Путеводитель предпринимателя, 2020)
The article considers the problem of risks completion construction and commissioning of facilities. On an example of an object transport are considered insurance conditions and requirements for the safety of installations affecting contract terms. The article shows the expediency of organizing interaction insurance company and contractors